Reassessing the Load Capacity Curve Hypothesis in ASEAN-5: Exploring Energy Intensity, Trade, and Financial Inclusion with Advanced Econometric Techniques - Kurniawati, Tri; Rahmizal, Maizul; Ridwan, Mohammad; Aspy, Nazhat Nury; Mahjabin, Tasfia; Eleais, Md.; Ridzuan, Abdul Rahim (International Journal of Energy Economics and Policy, 2025)
This study investigates how economic growth, energy intensity, financial inclusion, and trade globalization impact the load capacity factor in the ASEAN-5 region. Using data from 2000 to 2022 from reputable databases, the study analyzed the load capacity curve (LCC) hypothesis through comprehensive statistical analysis. Several diagnostic tests, such as cross-sectional dependence, slope homogeneity, unit root, and cointegration, to select a suitable long-run estimation model were conducted. The study utilized the Driscoll-Kraay standard error (DKSE) approach to address identified issues like cross-sectional dependence, heterogeneity, and unit root problems. DKSE estimation showed that the LCC hypothesis was not present in the ASEAN-5 region. It is worth noting that an inverted-U-shaped relationship between per capita income and the load capacity factor was found, emphasizing the complexity of economic dynamics in the region. Furthermore, the analysis revealed a strong correlation between energy intensity and the load capacity factor, with trade globalization having a significant negative effect. Surprisingly, financial inclusion did not show a significant correlation with the load capacity factor, highlighting the intricate role of financial accessibility in economic performance. To enhance the strength of the DKSE estimation, the study also utilized quantile regression analysis, which supported the results of the DKSE approach. The study confirmed that the LCC hypothesis is not applicable in the ASEAN-5 region and offered a more detailed analysis of the varying effects of energy intensity and trade globalization at different levels. Conclusively, this study provides valuable insights into the complex relationships among economic growth, energy intensity, financial inclusion, and trade globalization in the ASEAN-5 region. A thorough analytical approach enhances comprehension of sustainable development and economic resilience in the region, guiding policy decisions and future research efforts.